The Effect of Loyalty Points, Tiered Membership, Gamification, and Free Shipping on Customer Retention: A Study of Loyalty Programs in Online Shopping Applications - Hamdan Hamdan; Hapzi Ali (Green Publisher, 2025)
This study investigates the effect of various marketing strategies on customer retention in online shopping platforms. Specifically, it examines the influence of loyalty points, tiered membership, gamification, and free shipping. The results indicate that loyalty points, tiered membership, and gamification do not have a significant impact on customer retention, suggesting that incentive programs based on point accumulation, membership status, or game elements alone are insufficient to drive repeat purchase behavior. In contrast, free shipping has a positive and significant effect, highlighting that direct economic incentives providing tangible benefits are more effective in fostering customer loyalty. These findings imply that e-commerce managers should prioritize strategies offering immediate economic value, such as free shipping, to increase repeat purchases. Additionally, traditional loyalty programs and gamification elements should be restructured or combined with tangible rewards and clearly communicated benefits to enhance their effectiveness in retaining customers. This study contributes to a better understanding of consumer behavior in online retail and provides practical guidance for designing retention strategies that align with customer preferences and motivations.